Water Leakage Pre-Localization in Drinking Water Networks via the Cosmic-Ray Neutron Sensing Technique - Luca Morselli; Federica Lorenzi; Andrea Basso; Luca Stevanato (Engineering Proceedings)
Water leaks in drinking water networks contribute significantly to water losses and pose challenges to infrastructure sustainability. This study introduces a novel approach using Cosmic-Ray Neutron Sensing (CRNS) for pre-localizing leaks. We present a CRNS-based roving system that can detect the neutrons and muons produced by cosmic rays, providing real-time, below-ground water content data while addressing local variations. These data are analyzed using a one-class Support Vector Machine trained in an unsupervised manner. Finally, a brief overview of a proof of concept of the method conducted in a water district in Northern Italy is shown, highlighting preliminary results alongside some limitations.